REVISION OF DISSOCHAETA (MELASTOMATACEAE) IN JAVA, INDONESIA - ABDULROKHMAN KARTONEGORO; JAN FRITS VELDKAMP (Reinwardtia, 2010)
KARTONEGORO, A. & VELDKAMP, J.F. 2010. A revision of Dissochaeta (Melastomataceae) in Java. ReinwardtiaÂ 13(2): 125-145. - There are 12 species of Dissochaeta (Melastomataceae) in Java, Indonesia: D. bakhuizenii, D. bracteata, D. decipiens, D. fallax, D. gracilis, D. inappendiculata, D. intermedia, D. leprosa, D. monticola, D. reticulata, D. sagittata and D. vacillans. Diplectria and Macrolenes are regarded as separate genera and species traditionally classified within the latter have not been included. Dissochaeta leprosa, D. reticulata, and D. sagittata are reinstated as species. Dissochaeta gracilis is the most common species of Dissochaeta and D. bracteata is the rarest one. There are no endemics for the island. Each taxon is provided with literature references, synonymy, morphological descriptions, distribution, ecological habitat, collector's notes, and notes. An identification key and a list of collections seen are included